- 41

- 0

Hello, We proved something during the course but I totally forgot how to do it..

Prove that Planck's Law E=h*u is deduced from the equation of Doppler effect u'=u*√((1-β)/(1+β))

Lorentz transformation

If we take a beam of light of frequency u and an observer with speed Bc

I don't know if it's correct..

u'=u√((1-β)/(1+β))

E'=y(E-B*Px*c)

And px*c=E so

E'=y(E-BE)

=yE(1-B)

=E√((1-β))/(√((1-β)/(1+β)))

=E√((1-β))/√(1+β)

E'=E*u'/u

E'*u=E*u'

E'/u'=E/u

E/u=cste=h ?

**1. Homework Statement**Prove that Planck's Law E=h*u is deduced from the equation of Doppler effect u'=u*√((1-β)/(1+β))

**2. Homework Equations**Lorentz transformation

**3. The Attempt at a Solution**If we take a beam of light of frequency u and an observer with speed Bc

I don't know if it's correct..

u'=u√((1-β)/(1+β))

E'=y(E-B*Px*c)

And px*c=E so

E'=y(E-BE)

=yE(1-B)

=E√((1-β))/(√((1-β)/(1+β)))

=E√((1-β))/√(1+β)

E'=E*u'/u

E'*u=E*u'

E'/u'=E/u

E/u=cste=h ?

Last edited: